2011
DOI: 10.1111/j.1439-0507.2011.02028.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of licorice compounds licochalcone A, glabridin and glycyrrhizic acid on growth and virulence properties of Candida albicans

Abstract: Candida albicans is the predominant causal agent of candidiasis. Its ability to form hyphae and biofilm has been suggested to be key virulence factors. In this study, we investigated the effect of major licorice compounds licochalcone A, glabridin and glycyrrhizic acid on growth, biofilm formation and yeast-hyphal transition of C. albicans. The synergistic effect of licorice compounds with the antifungal drug nystatin was also evaluated. Minimal inhibitory concentrations (MICs) for C. albicans were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 21 publications
1
66
0
Order By: Relevance
“…Here, we demonstrated that Gla had weak antifungal activity against different fungi such as Candida species and C. neoformans, consisting with the previous reports [24], [25],[29],[30]. When combining with FLC, Gla exerted a strong synergistic antifungal effects at lower concentrations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Here, we demonstrated that Gla had weak antifungal activity against different fungi such as Candida species and C. neoformans, consisting with the previous reports [24], [25],[29],[30]. When combining with FLC, Gla exerted a strong synergistic antifungal effects at lower concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have been reported that the alcohol or ethanol extract of the roots of G. glabra possessed weak antifungal activity against C. albicans , Arthrinium sacchari , Chaetonmium funicola and various filamentous fungi [24], [29], [30]. Synergistic activity of Gla and nystatin against oral C. albicans has been demonstrated previously [25]. But to our knowledge, there was no investigation on the combination of Gla and FLC against fungi.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The main active ingredient in licorice is Licochalcone-A (Lico-A; (E)-3-[4-hydroxy-2-methoxy-5-(2-methylbut-3-en-2-yl)phenyl]-10-(4-hydroxyphenyl)prop-2-en-1-one), a natural phenolic chalconoid (Cho et al, 2014). According to recent studies, Lico-A has antioxidant (Fu et al, 2013), antiviral (Adianti et al, 2014), anti-inflammatory (Chu et al, 2012; Fu et al, 2013), antimicrobial (Messier and Grenier, 2011), antimalarial (Mishra et al, 2009), antiangiogenic (Kim et al, 2010), and osteogenic activities (Kim et al, 2012). Furthermore, Lico-A reportedly has anticancer activity in various cancers types such as oral (Kim et al, 2014), bladder (Yuan et al, 2013), ovarian (Lee et al, 2012), gastric (Xiao et al, 2011), colon (Lee et al, 2008), and prostate (Fu et al, 2004; Yo et al, 2009) cancer as well as in hepatocellular carcinoma (Choi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Searching for new strategies for inhibition of biofilm are becoming highly necessary (Kiedrowski and Horswill, 2011;Shunmugaperumal, 2010). In recent years, the efficiency of plant components on inhibition of biofilm has attracted more and more attention (Messier and Grenier, 2011;Sandasi et al, 2010;Xing et al, 2012). Essential oils from plants have been known to possess antibacterial, antifungal and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%